Spontaneous Periodic Hypothermia: Diencephalic Epilepsy. Issue 5868 (23rd June 1973) - Fox, R. H.; Wilkins, D. C.; Bell, J. A.; Bradley, R. D.; Browse, N. L.; Cranston, W. I.; Foley, T. H.; Gilby, E. D.; Hebden, Ann; Jenkins, B. S.; Rawlins, M. D.
Abstract : The case of a patient with episodic hypothermia and profuse sweating believed to be due to diencephalic epilepsy is reported. Despite intensive investigations no other manifestations of hypothalamic dysfunction were found. Conventional antiepileptic drugs were without effect but the patient was successfully treated by total sympathectomy.